Real-time analysis of the homogeneous and heterogeneous reactions of pyrene with ozone by SPAMS and CRD-EAS. (November 2019) - Qi, Xue; Pang, Xinglong; Hong, Yi; Wang, Yaliang; Lou, Shengrong; Feng, Jialiang; Cheng, Ping; Zhou, Zhen
Abstract: Single particle aerosol mass spectrometry (SPAMS) and Cavity ring-down aerosol extinction albedo spectroscopy (CRD-EAS) were applied in this work to real-time investigate the chemical and physical characteristics of the homogeneous and heterogeneous reactions of O3 with pyrene in a Teflon reaction chamber. Suspended pyrene coated polystyrene latex spheres (PSLs) were generated by vaporization-condensation. Ozonation products and particle size distribution during the reactions were detected in real-time using a SPAMS instrument. Among these products, the peaks at m / z of 262 and 278, assigned to 4, 5, 9, 10-dipyrenequinone and 1-hydroxy-4, 5, 9, 10-dipyrenequinone, respectively, were first detected to our knowledge. The mechanism for the formation of reaction product was also proposed based on the real time monitoring. With increasing the ozone concentration, the size growth of the original pyrene-coated particles and the formation of new fine particles and size growth were observed continuously. The optical characteristics were also investigated using a laboratory-developed CRD-EAS instrument. The extinction and scattering coefficients were observed to increase approximately five and four times, respectively. The absorption coefficient also increased because more polar oxidation products coated on the particles exhibiting higher light absorption ability than pyrene, and meanwhile, the single scattering albedo reduced from 0.88 to 0.77 which indicated the reactions could cause positive climate forcing. Using the on-line mass spectrometry and optic spectroscopy instruments, a systematic analysis method was developed to characterize the chemical and physical properties of homogeneous and heterogeneous reactions in real-time, which will help to investigate and understand the formation of new particles and particle growth in the atmosphere. Graphical abstract: SPAMS and CRD-EAS were applied in this work to real-time investigate the chemical and physical characteristics of the homogeneous and heterogeneous reactions of O3 with pyrene in a Teflon reaction chamber. Image 1 Highlights: Suspended pyrene coated polystyrene latex spheres were generated by vaporization-condensation. The ozonation products and particle size distribution were detected in real-time using a SPAMS instrument. The optical characteristics were investigated using a laboratory-developed CRD-EAS instrument. A systematic analysis method was provided to study the new particle formation and particle growth.